Vibrational Resonance in the Classical Morse Oscillator Driven by Narrow-Band and Wide-Band Frequency Modulated Signals - S. Guruparan; B. Ravindran Durai Nayagam; Chinnathambi Veerapadran; S. Rajasekar (Chemistry Department, The University of Brawijaya, 2016)
The phenomenon of vibrational resonance (VR) in the classical Morse oscillator influenced by narrow band and wide band frequency modulated signals is numerically studied. Vibrational resonance is found to occur when the amplitudes f and g and frequencies ω and Ω of the signals are varied. The dynamics of the system is studied in the presence of both signals separately. Vibrational resonance and dynamics of the system are characterized using the response amplitude and bifurcation diagram.